Response to Rv2628 latency antigen associates with cured tuberculosis and remote infection - Goletti, D; Butera, O; Vanini, V; Lauria, F N; Lange, C; Franken, K L M C; Angeletti, C; Ottenhoff, T H M; Girardi, E (The European respiratory journal, 2010)
Interferon-gamma release assays based on region of difference 1 antigens have improved diagnosis of latent tuberculosis infection (LTBI). However, these tests cannot discriminate between recently acquired infection (higher risk of progression to active tuberculosis) and remote LTBI. The objective of the present study was to evaluate the T-cell interferon-gamma responses to Mycobacterium tuberculosis DosR-regulon-encoded antigens (latency antigens) compared with QuantiFERON TB-Gold In-Tube (QFT-GIT) in subjects at different stages of tuberculosis. A total of 16 individuals with remote LTBI and 23 with recent infection were studied; 15 controls unexposed to M. tuberculosis and 50 patients with active tuberculosis and 45 with cured tuberculosis were also analysed. The results indicated that subjects with remote LTBI showed significantly higher whole-blood interferon-gamma responses to M. tuberculosis latency antigen Rv2628 than did individuals with recent infection, active tuberculosis and controls (p<0.003), whereas no significant differences between these groups were found for other latency antigens tested (Rv2626c, Rv2627c, Rv2031c and Rv2032). The proportion of responders to Rv2628 was five-fold higher among QFT-GIT-positive-individuals with remote infection than among those with recently acquired infection. These data suggest that responses to M. tuberculosis latency antigen Rv2628 may associate with immune-mediated protection against tuberculosis. In contact-tracing investigations, these preliminary data may differentiate recent (positive QFT-GIT results without responses to Rv2628) from remote infection (positive to both tests).